Matrix Implementation of Moore FSM with Encoding of Collections of Microoperations - Barkalov, A. A.; Titarenko, L.; Hebda, O. P.; Soldatov, K. (ХНУРЭ, 2009)
The method is proposed for reduction of hardware amount in logic circuit of Moore finite state machine. The method is oriented on customized matrix technology. It is based on representation of the next state code as a concatenation of code for class of collection of microoperations and code of the vertex. Such an approach allows elimination of dependence among states and microoperations. As a result, both circuits for generation of input memory functions and microoperations are optimized. An example of the proposed method application is given.
Keywords: pseudoequivalent states; Moore FSM; logic circuit; graph-scheme of algorithm; сustomized matrices